Optimal maintenance planning for offshore wind farms under an uncertain environment - Su, Tai-Sheng; Weng, Xin-Yu; Yu, Vincent F.; Wu, Chin-Chun (Ocean engineering, 2023)
The operation and maintenance costs of wind power generation systems can be reduced through the implementation of maintenance policies at suitable procurement indenture and maintenance levels. Purchasing components involves uncertainties associated with cost and component reliability due to objectives which frequently lack precision. In order to solve fuzzy multi-objective lot-sizing decisions of spare parts for a long term predictive maintenance planning problem in offshore wind farms, this study develops a novel fuzzy multi-objective linear programming model with piecewise linear membership function and S-curve membership function to simultaneously evaluate maintenance cost and system reliability. This model integrates multi-OWT (offshore wind turbines), multi-component, multi-supplier, and component reliability functions for offshore wind systems under an uncertain environment. The analytical results can help operation and maintenance managers to systematically analyze the cost-effectiveness and system reliability of predictive maintenance planning in practical applications. •The predictive maintenance planning problem in offshore wind farms uncertain environment.•Fuzzy multi-objective linear programming model with the piecewise linear membership function and S-curve membership function.•An interactive decision-making procedure facilitating the fuzzy environment.